2023
DOI: 10.3389/fpls.2023.1152419
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in agriculture – a potential novel mechanism for the delivery of human pathogens onto crops

Richard S. Quilliam,
Chloe J. Pow,
Dativa J. Shilla
et al.

Abstract: Mulching with plastic sheeting, the use of plastic carriers in seed coatings, and irrigation with wastewater or contaminated surface water have resulted in plastics, and microplastics, becoming ubiquitous in agricultural soils. Once in the environment, plastic surfaces quickly become colonised by microbial biofilm comprised of a diverse microbial community. This so-called ‘plastisphere’ community can also include human pathogens, particularly if the plastic has been exposed to faecal contamination (e.g., from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Studies have reported that primary and secondary sources are the two main pathways through which plastic contaminants can enter agriculture. Both sources can be further defined as (1) primary sources include leakage or entry of plastic pollution from agricultural activities (such as mulching, irrigation, and fertigation) and ( 2) secondary sources include leakage or entry of plastic pollution from non-agricultural activities (such as plastic particles blowing in the air in urban areas and landfills) [152][153][154][155][156][157]. Climate variables such as high temperature, solar radiation, precipitation, and wind are among the factors responsible for physical weathering, aging, and quality deterioration of plastics in soils [158][159][160][161].…”
Section: Sources Of Plastic Pollution In Agriculture and Its Adhesive...mentioning
confidence: 99%
“…Studies have reported that primary and secondary sources are the two main pathways through which plastic contaminants can enter agriculture. Both sources can be further defined as (1) primary sources include leakage or entry of plastic pollution from agricultural activities (such as mulching, irrigation, and fertigation) and ( 2) secondary sources include leakage or entry of plastic pollution from non-agricultural activities (such as plastic particles blowing in the air in urban areas and landfills) [152][153][154][155][156][157]. Climate variables such as high temperature, solar radiation, precipitation, and wind are among the factors responsible for physical weathering, aging, and quality deterioration of plastics in soils [158][159][160][161].…”
Section: Sources Of Plastic Pollution In Agriculture and Its Adhesive...mentioning
confidence: 99%
“…In addition to the negative effects of microplastics on soil health and productivity, there are also concerns regarding their consequences to ecosystems and the exposure of humans through food and water chains. In a recent study, researchers investigated the nature of microbial biofilms—the so-called “plastisphere”—that colonize microplastic surfaces [ 91 ]. They found that this community, when attached to plastic that has come into contact with feces (such as those from organic manures, wastewater, or animal waste), as is often the case for agricultural plastics, might be associated with human pathogens.…”
Section: Microplastics Soil Remediation and Restoration Strategiesmentioning
confidence: 99%
“…Due to their small size, MPs possess a significantly larger surface area, facilitating the adsorption of a wide range of pollutants on their often-hydrophobic surfaces. These tiny particles enter diverse environmental compartments, from rivers and soils to the atmosphere, and from the deepest depths of the oceans to the most remote areas of the polar regions [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%